Polymorphism in propyl gallate recrystallized with acetone - Gálico, D. A. [UNESP]; Nova, C. V. [UNESP]; Bannach, G. [UNESP] (Springer Nature, 2017)
A new polymorphic form of the synthetic antioxidant propyl gallate was obtained by the recrystallization of the compound in acetone. The new form was characterized by thermogravimetry, differential scanning calorimetry, X-ray powder diffractometry, and near- and middle-infrared region spectroscopy. While the commercial form of propyl gallate starts to melt at 145 °C with the maximum temperature of the peak at 150 °C, the recrystallized form starts to melt at 140 °C with the maximum temperature of the peak at 148.8 °C. The two forms differ much in the X-ray powder diffractograms pattern, confirming the change in the long-distance interactions in both forms but the near- and middle-infrared region spectroscopy shows that no difference occurs in the inter- and intramolecular interactions.
Keywords: Food additive; Polymorphism; Propyl gallate; Thermal behavior